THE EFFECT OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT CLASS IIB GUNUNG SUGIH CORRECTIONAL INSTITUTION - Syahfery, Ahmad; Romli, Khomsahrial; Barusman, M. Yusuf Sulfarano (Program Studi Magister Manajemen, 2024)
Organizations possess interconnected structures and goals, relying heavily on human communication to coordinate their activities. This study aims to examine the influence of leadership style on employee performance, the impact of work motivation on employee performance, and the combined effect of both variables on the performance of employees at the Class IIB Correctional Institution of Gunung Sugih. The research employed a survey method with both qualitative and quantitative approaches. The analysis revealed that leadership style and work motivation simultaneously have a significant effect on employee performance, with a correlation coefficient (r) of 0.673 and a contribution of 39.4%. The F-test result showed an F-value of 5.538, which exceeds the F-table value of 2.40 at a 5% significance level, indicating that the alternative hypothesis is accepted and the null hypothesis is rejected. In conclusion, leadership style and work motivation significantly influence employee performance improvement. Therefore, it is recommended that both aspects be further enhanced, underperforming employees be provided with appropriate training, supervisory control be strengthened, and a fair reward and punishment system be implemented.